2002
DOI: 10.1007/s00405-002-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of inducible nitric oxide synthase and 3-nitrotyrosine in recurrently inflamed, human palatine tonsils

Abstract: The purpose of this study was to evaluate the possible involvement of nitric oxide and its toxic metabolite -peroxynitrite -in the pathogenesis of recurrent tonsillitis. Tonsil specimens with recurrent inflammation were obtained from patients who required tonsillectomies as surgical treatment for their conditions. The relatively normal tonsils were obtained from patients who underwent uvulo-palato-pharyngoplasty for habitual snoring or obstructive sleep apnea. The sites of inducible nitric oxide synthase (iNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…The mechanisam of chronic tonsillitis is not yet clear. Nitric-oxide and its toxic metabolities are assumed as factors in chronic tonsillitis development (2). On the other hand enzyme arginase is in some relation with tonsillar hypertrophy (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisam of chronic tonsillitis is not yet clear. Nitric-oxide and its toxic metabolities are assumed as factors in chronic tonsillitis development (2). On the other hand enzyme arginase is in some relation with tonsillar hypertrophy (3).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic studies point to relation of enzymes such superoxide dismutase, nitric oxide synthase and arginase in chronic tonsillitis and tonsillar hypertrophy (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested that the NO pathway may be involved in the pathogenesis of chronic adenotonsillar disease on the basis of the finding of higher eNO levels in a small group of adults with recurrent tonsillar infections (11), and their normalization in the same patients after tonsillectomy (7). In addition, the enhanced immunolocalisation of iNOS and the metabolites of NO-pathway 3-nitrotyrosine (a footprint of the highly reactive peroxynitritre induced by a NO reaction to reactive oxygen species) has been found in specimens of recurrently inflamed tonsils taken from adults (9). With regard to children, who are the most affected by chronic adenotonsillar disease, Unal et al (10) reported increased venous blood levels of iNOS and arginase (a precursor of NO synthesis) in 22 children with chronic adenotonsillar hypertrophy, without mentioning infections.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the NO pathway may play a role in chronic tonsillar disease (7,(9)(10)(11) as Kasperska-Zajac et al (11) found increased exhaled NO (eNO) levels in 32 adults with recurrent tonsillitis, and have recently reported a significant post-tonsillectomy reduction in eNO levels to values that were not different from those of healthy controls (7). Furthermore, there have been sporadic reports (9)(10) of an increase in the expression of inducible NO synthase (iNOS, one of the enzymatic forms involved in NO production) and the molecules involved in the NO pathway in the tonsils of adults with recurrent inflammation, as well as in venous blood samples taken from children with chronic adenotonsillar hypertrophy.…”
mentioning
confidence: 99%
“…Some authors have investigated the possible involvement of nitric oxide, 7 9 a highly reactive biological mediator naturally released by human airways that can be considered a marker of airway inflammation 10 . However, the findings of such studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%